A single centre study of 41 cases on the use of porous tantalum metal implants in acetabular revision surgery - Christoph Theil; Tom Schmidt-Braekling; Georg Gosheger; Burkhard Moellenbeck; Jan Schwarze; Ralf Dieckmann (BMC Musculoskeletal Disorders, 2019)
Abstract Background This study aims at investigating cup survival of porous tantalum revision cups and identifies risk factors for failure. Methods We retrospectively reviewed 41 patients treated between 2010 and 2012. Main indications were aseptic loosening in 83% and two-stage exchange after periprosthetic joint infection in 17% of cases. Mean follow-up period was 72 months. Femoral megaprostheses were used in 13% of cases. Most defects were classified as Paprosky 3b (29%). Function was assessed using the Harris Hip score. Results Aseptic cup survivorship was 80% at 104 months (95% Confidence Interval 67.4–92.4). Overall implant survival was 73%. Major bone loss defects (Paprosky types 2c to 3b) were associated with a significantly higher rate of failure than minor defects (P = 0.002). There were eight cases of aseptic loosening (19.5%) and two of infection (4.9%). Previous surgeries, indication for acetabular revision, patient-related risk factors and use of megaprostheses did not significantly influence implant survival. The Harris Hip Score improved from a median of 40 (Interquartile range 31–45) to 82 (interquartile range 65–88) postoperative (P < 0.0001). Conclusions In summary, the use of porous tantalum metal implants in acetabular revision surgery achieves good to excellent short- term and mid-term functional results and an acceptable complication rate relative to the extent of defect and previous surgery. However, one should be aware of potential limitations of the implants in addressing large defects and discontinuity.